Dust explosion and fire prevention handbook : a guide to good industry practices - Cheremisinoff, Nicholas P. (Engineering professional collection, 2014)
Discussing the causes, repercussions, and prevention of dust explosions and fires, this thorough book covers the most up-to-date information and safety guidelines as well as a glossary of terms for easy reference and an appendix outlining the best practices for industrial applications. --